A magnetic CoFe2O4–CNS nanocomposite as an efficient, recyclable catalyst for peroxymonosulfate activation and pollutant degradation. Issue 87 (4th December 2017) - Chen, Chang-Bin; Zhang, Feng; Li, Chen-Xuan; Lu, Jia-Yuan; Cui, Shuo; Liu, Hou-Qi; Li, Wen-Wei
Abstract : An efficient, stable, easily recoverable hybrid nanomaterial for heterogeneous activation of PMS and sulfonamide degradation. Abstract : Sulfate radical (SO4 ˙ − ) based advanced oxidation processes allow efficient degradation of refractory organics, but efficient, low-cost, and robust catalysts for such processes are still lacking. In this work, a magnetically recoverable heterogeneous catalyst was fabricated by immobilizing spinel cobalt-ferrite (CoFe2 O4 ) particles on graphitic carbon nitride nanosheets (CNS) using a low-cost, one-step solvothermal method. In the CoFe2 O4 –CNS nanocomposite, the CoFe2 O4 particles were evenly-distributed on the CNS surface, giving the nanocomposite a high specific surface area and significantly raised activity for peroxymonosulfate (PMS) activation and sulfonamide degradation compared to the bare CoFe2 O4 NPs, which were considerably aggregated. In addition, the CoFe2 O4 –CNS could be more efficiently separated under magnetic field and resuspended compared with the bare CoFe2 O4 due its larger sizes and no agglomeration. A stable activity of the nanocomposite catalyst during repeated use was also demonstrated. Our results imply high potential of CoFe2 O4 –CNS for sustainable water treatment and environmental remediation applications.